Accessory breast tissue (Mammae Aberrans) presenting as an axillary mass: A case report - Anak Agung Ary Yuliani; Anak Agung Ngurah Pretangga (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Mammae aberrans, also known as accessory or ectopic breast tissue, is a rare congenital condition that arises due to incomplete regression of the embryonic mammary ridge. Although it is often asymptomatic, in some cases it may enlarge, become tender, or resemble other axillary abnormalities, which can complicate diagnosis and management. Given its rarity and similarity to other axillary lesions, clinicians must exercise caution to ensure accurate diagnosis and appropriate management. Purpose: To describe in detail the clinical features, diagnostic process, and surgical management of a 27-year-old female patient presenting with an axillary mass later identified as mammae aberrans. Method: The report is based on a single clinical case involving a young female patient who presented with a progressively enlarging mass in her right axilla. The diagnostic process included physical examination, ultrasonography, and histopathological analysis. The patient underwent surgical excision of the mass under general anesthesia, followed by postoperative observation and follow-up to monitor recovery and possible recurrence. Results: Clinically, the mass was firm, immobile, and measured approximately 12 × 8 × 6 cm. Ultrasonography indicated fibro-glandular tissue, and the histopathological examination confirmed the diagnosis of mammae aberrans. The surgical removal of the mass was successful, with the patient showing good postoperative recovery. No pain, complications, or recurrence were reported during follow-up visits. Conclusion: Highlights the importance of considering accessory breast tissue in the differential diagnosis of axillary masses, especially in women of reproductive age. Early and accurate diagnosis, followed by appropriate surgical management, can lead to complete recovery, prevent misdiagnosis, and improve cosmetic and psychological outcomes for the patient.